Dung beetles can sow: the potential of secondary seed dispersers to assist ecological restoration - Almeida, Hernani A.; Antonini, Yasmine; Tavares Junior, Cláudio; Braga, Rodrigo F.; Silva, Pedro G.; Beiroz, Wallace (Ecological entomology, 2022)
1. Restoration of disturbed environments in which soil surface layers have been removed is challenging and its success depends on the characteristics of the exposed soil layers and neighbour organisms. Dung beetles are important elements in the restoration of degraded habitats as secondary seed dispersers. 2. In this study, we first assessed how the removal of upper soil layers affected the assemblage of dung beetle compared to adjacent reference areas without soil removal. We also evaluated the efficiency of dung beetles as secondary seed dispersers by experimentally testing their effect on the germination of wolf apple seeds (Solanum lycocarpum). 3. Degraded areas harboured a different dung beetle assemblage compared to the reference area, with a predominance of habitat generalist species. In addition, we found higher abundance and richness of dung beetles in the degraded than in reference areas. Despite dung removal being similar between areas, more seeds were removed in the reference area. 4. Dung beetles, especially rollers, positively influenced the probability of wolf apple seed germination in the degraded environment by up to 5%; germination occurred in 27% of treatments with dung beetle presence and no germination occurred when beetles were excluded. 5. Therefore, promoting the attraction of dung beetles from reference areas, together with other techniques that enhance primary seed dispersion, mainly by mammals and birds, could potentially increase the success of projects to restore areas with degraded soil. Dung beetles increase the probability of seed germination. Roller dung beetles are important for seed dispersal and germination. Neighbour areas are source of organisms and functions for degraded areas.